Efficient control of a nonlinear double-pendulum overhead crane with sensorless payload motion using an improved PSO-tuned PID controller - H. I. Jaafar; Z. Mohamed; N. A. Mohd Subha; A. R. Husain; F. S. Ismail; Liyana Ramli; M. O. Tokhi; M. A. Shamsudin (SAGE Publications Ltd, 2024)
Volume: 25 issue: 4, page(s): 907-921